Jarimatika Method: Effectiveness in Increasing Motivation to Learn Multiplication Counting Operations with Creative Songs - Rahayu, Anggun Ika; Utami, Ratnasari Dyah (Universitas Pendidikan Ganesha, 2022)
Teachers are highly recommended to carry out interactive and fun learning, delivering boring material will make the teaching and learning process difficult for students to understand, so that the impact on mathematics learning outcomes will be lower. This study aims to analyze the effectiveness of the song creation-based jarimatika method to increase students' motivation for multiplication counting operations. This research is a quantitative type of research with an experimental design. The subjects of this study were 4th grade students in elementary schools. Methods of collecting research data with questionnaires and tests. The research instrument is a questionnaire with questions for learning motivation variables. Data analyses consist of descriptive analysis and comparative analysis. The results showed that after using the creative song-based jarimatika method on the motivation to learn multiplication counting operations, the experimental class students' learning motivation increased by an average of 24, while the increase in the control class was 28. Comparative analysis resulted that the use of the song creation-based jarimatika method on the motivation to learn arithmetic operations effective multiplication. Comparative analysis of sig. 2-tailed control and experimental class 0.151 is not significant. Sig 2-tailed before treatment in the experimental class and the control class 0.035. Sig. 2-tailed learning motivation before and before the control class 0.000. The difference in motivation between the control and experimental classes is sig. 2-tail 0.047. It can conclude that the song-based jarimatika method of creation on the motivation to learn multiplication arithmetic operations is effective in increasing motivation for multiplication operations.